Respuesta :

To answer this question, we need to identify the formula for the line equation in the graph.

We can see that if we take two points from the graph, we have:

(0, 0)

(1, 1)

Then, to find the equation for this line, we need to find the slope of the line first:

(0, 0) ---> x1 = 0, y1 = 0

(1, 1) ---> x2 = 1, y2 = 1

The slope is:

[tex]m=\frac{y_2-y_1}{x_2-x_1}=\frac{1-0}{1-0}\Rightarrow m=1[/tex]

Applying the point-slope form of the line, we have:

[tex]y-y_1=m(x-x_1)\Rightarrow y-0=1(x-0)\Rightarrow y=x[/tex]

Then, the function is y = x (as we can check from the graph).

Then, we have that:

[tex]h(x)=-f(x)+3[/tex]

And

[tex]f(x)=x\Rightarrow-f(x)=-x[/tex]

Therefore

[tex]h(x)=-x+3[/tex]

Thus, we need to graph this line using the previous equation. We need to find the x-intercept for the line (the value of x when y = 0), and the y-intercept for the line (the value of y when x = 0). Then, we have:

[tex]y=-x+3,y=0\Rightarrow0=-x+3\Rightarrow x=3[/tex]

Then, the x-intercept is (3, 0).

And the y-intercept is (x = 0):

[tex]y=-(0)+3\Rightarrow y=3[/tex]

Hence, the y-intercept is (0, 3).

Therefore, if we put these two points on a graph (3, 0) and (0, 3), the graph will be:

We can see that the line has a different slope, and we can see that the y-intercept is 3, which corresponds with the new function.

Ver imagen LashonB49226
Ver imagen LashonB49226
ACCESS MORE
EDU ACCESS
Universidad de Mexico